Public Perception of Degenerative Diseases in Medan City in Choosing Herbal Medicine - Sri Lestari Ramadhani Nasution; Tasyaa Dwi Hardiyani; Ermi Girsang (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Herbal remedies have gained increasing popularity, particularly among individuals with degenerative diseases. This study aims to explore the factors influencing the use of herbal medicine among the degenerative disease community in Medan City, with a specific focus on internal factors such as knowledge and awareness, as well as external factors including social and cultural influences. The research involved 12 informants, comprising members of the herbal medicine user community, family members, and herbal medicine vendors. Data were collected through in-depth interviews and analyzed using the Miles and Huberman qualitative analysis framework. The findings reveal that public perception regarding the use of herbal medicine for degenerative diseases in Medan City is shaped by a relatively high level of knowledge and awareness. Most respondents reported acquiring information from friends and social media, underscoring the influential role of social networks and digital platforms in disseminating health-related information. Social and cultural factors also significantly affect decision-making processes. While traditional beliefs were not identified as dominant influences, support from family, friends, and the broader community emerged as critical motivators in the choice to use herbal remedies.In conclusion, the decision to use herbal medicine among individuals with degenerative diseases in Medan City is influenced by a combination of knowledge, awareness, and socio-cultural factors. A solid understanding of the benefits and risks associated with herbal medicine, coupled with high awareness, reinforces individuals' decisions. Moreover, social support from family, peers, and the community plays a vital role in enhancing trust and confidence in herbal therapies. It is recommended that reliable and evidence-based information about herbal medicine be disseminated more widely through social media and community networks. Additionally, public education and training initiatives should be implemented to promote the safe and effective use of herbal remedies, thereby maximizing their potential benefits in community health settings. Keywords: Herbal Medicine, Degenerative Diseases, Knowledge, Social Influence, Public Awareness.